EFFECT OF HIGH DOSES OF ROSUVASTATIN IN MIAINDUCED OSTEOARTHRITIS - Bajaad, Jyoti; Kaur, Rajvinder; Bijjem, Krishna Reddy V. (Asian Journal of Pharmaceutical Research and Development, 2013)
Statins exert favorable effects on hyperlipidemia but may also possess anti-inflammatory effects. Here, we explored the effects of rosuvastatin in a model of Monosodium iodoacetate-induced arthritis in rat. Palmer et al. were unable to show any preventive effect using oral atorvastatin or subcutaneous rosuvastatin in murine collagen model. So the present study was designed to check effect of rosuvastatin at various doses in MIA –induced osteoarthritis.